Surf's up! - Barton, Chris (Barton, Chris. Mighty Truck., 2019)
Clarence joins his neighbor, Mr. Dent, and his cat Throttle for a day of surfing at the beach, but when Throttle gets into trouble and cannot swim, it's up to Clarence to save the day.